Prevalence and Role of Psychiatric Conditions in Patients Diagnosed with Anterior Knee Pain (192). Issue 10 (31st October 2021) - Swinehart, Steven; Bowman, Eric; Freeman, Thomas; Rees, Andrew; Harper, Holly; Coronado, Rogelio
Objectives: Anterior knee pain is a common musculoskeletal complaint with a multifactorial etiology. Psychiatric conditions may play a significant role in both the evolution of anterior knee pain and recovery from it. This retrospective, matched case-control study evaluates the prevalence of psychologic conditions in patients with anterior knee pain to assess their role as a potential contributor. Methods: 126 patients with anterior knee pain were retrospectively identified using ICD-10 codes and were individually matched to controls based on gender, age, and BMI. Patient demographics, surgical history, medications, and prior or current diagnoses related to musculoskeletal or psychiatric health were recorded. Demographic data between the anterior knee pain group and controls were evaluated using independent t-tests. Differences between the matched pairs related to psychiatric conditions and medication usage were evaluated using a McNemar Test. A subgroup analysis was also performed and defined by gender, age greater than or less than 35, and BMI greater than or less than 25. Results: Evaluation of demographic data between the anterior knee pain group and controls showed no difference with regards to age, gender, and BMI (p>0.05). Analysis of the 126 matched pairs demonstrated similar rates of psychiatric conditions and medication usage between the anterior knee pain group (23 patients, 18.3%) and the control group (18 patients, 14.3%). Statistically, there was no difference between the two groups (p = 0.472). A subgroup analysis also demonstrated no difference between the anterior knee pain group and controls when stratified by gender (Male [p = 0.80]; Female [p = 0.12]), age (< 35 [p = 1.00]; > 35 [p = 0.50]), and BMI (< 25 [p = 0.10]; > 25 [p = 0.82]). Conclusions: There was no difference in the prevalence of psychiatric conditions between patients with anterior knee pain and their controls. This suggests a low likelihood that the psychologic condition of patients with anterior knee pain differ from that of the general population and implies that psychologic conditions alone are unlikely to play an isolated role in the etiology of anterior knee pain.